Creation and implementation of a novel clinical workflow based on the AAST uniform anatomic severity grading system for emergency general surgery conditions. Issue 1 (8th September 2020) - Bessoff, Kovi E; Choi, Jeff; Bereknyei Merrell, Sylvia; Nassar, Aussama Khalaf; Spain, David; Knowlton, Lisa Marie
Abstract : Objective: Emergency general surgery (EGS) conditions encompass a variety of diseases treated by acute care surgeons. The heterogeneity of these diseases limits infrastructure to facilitate EGS-specific quality improvement (QI) and research. A uniform anatomic severity grading system for EGS conditions was recently developed to fill this need. We integrated this system into our clinical workflow and examined its impact on research, surgical training, communication, and patient care. Methods: The grading system was integrated into our clinical workflow in a phased fashion through formal education and a written handbook. A documentation template was also deployed in our electronic medical record to prospectively assign severity scores at the time of patient evaluation. Mixed methods including a quantitative survey and qualitative interviews of trainees and attending surgeons were used to evaluate the impact of the new workflow and to identify obstacles to its adoption. Results: We identified 2291 patients presenting with EGS conditions during our study period. The most common diagnoses were small bowel obstruction (n=470, 20.5%), acute cholecystitis (n=384, 16.8%), and appendicitis (n=370, 16.1%). A total of 21 qualitative interviews were conducted. Twenty interviewees (95.2%) had a positive impression of the clinical workflow, citing enhanced patient care and research opportunities. Fifteen interviewees (75.0%) reported the severity grading system was a useful framework for clinical management, with five participants (25.0%) indicating the system was useful to facilitate clinical communication. Participants identified solutions to overcome barriers to adoption of the clinical workflow. Conclusions: The uniform anatomic severity grading system can be readily integrated into a clinical workflow to facilitate prospective data collection for QI and research. The system is perceived as valuable by users. Educational initiatives that focus on increasing familiarity with the system and its benefits will likely improve adoption of the classification system and the clinical workflow that uses it. Level of evidence: Level III.